2020
DOI: 10.1155/2020/6485826
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Low-Salinity Water Flooding as a Tertiary Oil Recovery Technique

Abstract: In this project, low-salinity water flooding has been modeled on ECLIPSE black oil simulator in three cases for a total field production life of twenty-five years. In the first case, low-salinity water flooding starts fifteen years after secondary water flooding. For the second case, low-salinity water flooding starts five years after secondary water flooding and runs till the end of the field production life. For the third case, low-salinity water flooding starts five years after secondary water flooding, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, this model adds a separate salt phase to the existing phase and solves a mass conservation equation for each block in the reservoir model. More detailed information on LSWI modeling by the Eclipse program at various water concentrations is presented in previous works (Knut 2012;Xie et al 2015;Qiao et al 2016;Olabode et al 2020;Al-Ibadi et al 2021). In this work, in the used model, the minimum distance from the ground to the first layer of the reservoir was 2500 m, and in the deepest part of the reservoir was 3100 m. The reservoir model included nine producers and two injection wells completed at the top of the reservoir.…”
Section: Simulation Of Recovery Factor At Various Salt Concentrations...mentioning
confidence: 99%
“…Furthermore, this model adds a separate salt phase to the existing phase and solves a mass conservation equation for each block in the reservoir model. More detailed information on LSWI modeling by the Eclipse program at various water concentrations is presented in previous works (Knut 2012;Xie et al 2015;Qiao et al 2016;Olabode et al 2020;Al-Ibadi et al 2021). In this work, in the used model, the minimum distance from the ground to the first layer of the reservoir was 2500 m, and in the deepest part of the reservoir was 3100 m. The reservoir model included nine producers and two injection wells completed at the top of the reservoir.…”
Section: Simulation Of Recovery Factor At Various Salt Concentrations...mentioning
confidence: 99%
“…LSWF is a secondary and tertiary oil production technique that involves injecting diluted formation water, seawater, or smart water to enhance the oil recovery process. , Despite its cost-effectiveness, environmental benefits, and potential for up to 15% additional oil recovery, LSWF has not gained widespread operational acceptance and remains largely confined to experimental applications . The main challenge lies in upscaling the results of LSWF mechanisms studied across various reservoir scales to generate standardized operational parameters, reduce associated reservoir damage risks, and facilitate broader LSWF field implementation. , The commercialization and maturity of LSWF have been hindered by these challenges, but extensive microscale studies have revealed that wettability alteration plays a crucial role in LSWF interactions. As a result, modeling wettability alteration has become the primary focus when simulating LSWF in both core and large-scale models across different platforms. …”
Section: Introductionmentioning
confidence: 99%
“… 9 The main challenge lies in upscaling the results of LSWF mechanisms studied across various reservoir scales to generate standardized operational parameters, reduce associated reservoir damage risks, and facilitate broader LSWF field implementation. 4 , 10 12 The commercialization and maturity of LSWF have been hindered by these challenges, but extensive microscale studies have revealed that wettability alteration plays a crucial role in LSWF interactions. As a result, modeling wettability alteration has become the primary focus when simulating LSWF in both core and large-scale models across different platforms.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of salt causes an electrostatic repulsion of polymer chains, which leads to its contraction and the eventual loss of viscosity [14]. Simulation studies on low-salinity-water flooding have been considered by [15] to reduce the reservoir saline contents for light oil reservoirs with additional recoveries of 11% over water flooding, but the challenge with this option is low performance in medium to heavy oil reservoirs [16]. References [17][18][19] have experimentally investigated the oil recovery performances of polymer flooding options with a preconditioned reservoir with low salinity.…”
Section: Introductionmentioning
confidence: 99%